All-cause and cardiovascular mortality risk after surgery versus radioiodine treatment for hyperthyroidism. Issue 3 (8th November 2017) - Giesecke, P; Frykman, V; Wallin, G; Lönn, S; Discacciati, A; Törring, O; Rosenqvist, M
Abstract: Background: Little is known about the long-term side-effects of different treatments for hyperthyroidism. The few studies previously published on the subject either included only women or focused mainly on cancer outcomes. This register study compared the impact of surgery versus radioiodine on all-cause and cause-specific mortality in a cohort of men and women. Methods: Healthcare registers were used to find hyperthyroid patients over 35 years of age who were treated with radioiodine or surgery between 1976 and 2000. Comparisons between treatments were made to assess all-cause and cause-specific deaths to 2013. Three different statistical methods were applied: Cox regression, propensity score matching and inverse probability weighting. Results: Of the 10 992 patients included, 10 250 had been treated with radioiodine (mean age 65·1 years; 8668 women, 84·6 per cent) and 742 had been treated surgically (mean age 44·1 years; 633 women, 85·3 per cent). Mean duration of follow-up varied between 16·3 and 22·3 years, depending on the statistical method used. All-cause mortality was significantly lower among surgically treated patients, with a hazard ratio of 0·82 in the regression analysis, 0·80 in propensity score matching and 0·85 in inverse probability weighting. This was due mainly to lower cardiovascular mortality in the surgical group. Men in particular seemed to benefit from surgery compared with radioiodine treatment. Conclusion: Compared with treatment with radioiodine, surgery for hyperthyroidism is associated with a lower risk of all-cause and cardiovascular mortality in the long term. This finding was more evident among men. Abstract : Surgery preferable for men